Literacy Quebec Newsletter - Literacy Quebec (LQ) (2024)

Inclusive Mentorship Initiative - Townshippers' Association (2024)
This report provides an overview and evaluation of the 2023-2024 fiscal year ofTownshippers’ Association’s Inclusive Mentorship Initiative (IMI) funded by theSecrétariat aux relations avec les Québécois d’expression anglaise from December 2021to the present.
Keywords: Official Language Minority Community (OLMC)

Championing Early Literacy Through Libraries and Community Partnerships - Dixit, Aisha (QUESCREN Education and Vitality Forum 2023, 2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

Consultation prébudgétaire de Alphabétisation Québec 2023-2024 déposé au ministre des Finances du Québec et au ministre responsable des Relations avec les Québécois d’expression anglaise - Literacy Quebec (LQ) (2023)
Alphabétisation Québec/Literacy Québec est un regroupement national qui compte 15 organismes d’alphabétisation populaires. Fondé en 1980, il est accrédité au Programme d’action communautaire sur le terrain de l’éducation (PACTE) et reçoit un soutien financier pour appuyer sa mission globale de la part du ministère de l’éducation ainsi que du Secrétariat aux relations avec les Québécois d’expression anglaise. Le regroupement mène des actions pour conscientiser le public aux réalités de l'analphabétisme et pour promouvoir des opportunités d’apprentissage tout au long de la vie. Alphabétisation Québec offre du soutien, de l’accompagnement et de la formation continue à ses groupes membres. Ceux-ci sont des milieux de vie et des lieux de formation pour les adultes et les familles de toutes origines qui désirent acquérir, rehausser ou maintenir leurs compétences de base sur le plan de la lecture, l’écriture, la numératie ou la littératie numérique. Ils ont développé une approche unique d’éducation non formelle et informelle qui vise l’autonomisation et l’inclusion des personnes et qui est adaptée au rythme d’apprentissage des participants.

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

2022-2023 Activity Report - Literacy Quebec (LQ) (2023)

Literacy Quebec Newsletter : Special Edition - Literacy Quebec (LQ) (2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Society Pages - Morrin Centre (2022)

Society Pages - Morrin Centre (2022)

COVID-19 Survey Report II - Literacy Quebec (LQ) (2021)
While the pandemic has forced a lot of swift changes, the majority of Literacy Quebec's member organizations have been able to adapt. In fact, 8 out of 9 respondents claimed to have successfully transitioned at least some of their programs and services online. However, while most organizations were able to move to some type of online- learning model, a select few reported having no available tutors/volunteers. Some of the reasons ranged from a lack of interest (i.e. volunteers originally signed up to interact with others in person), or a lack of confidence in using technology.

Activity Report - Literacy Quebec (LQ) (2021)

Family Literacy Toolkit - Literacy Quebec (LQ) (2021)

Society Pages - Morrin Centre (2021)

Society Pages - Morrin Centre (2021)

Activity Report 2019-2020 - Jamaica Association of Montreal (JAM) (2020)

Annual Report 2019/2020 : 40th Anniversary Edition - Literacy Quebec (LQ) (Literacy Quebec, 2020)

Celebrating 40 Years - Literacy Quebec (LQ) (2020)
The year was 1980 and the world was undergoing massive change. CNN launched, the Rubik’s cube went on sale and the Iran-Iraq war began. Closer to home, Quebecers voted in a sovereignty referendum to remain part of Canada, while the sports scene saw the Montreal Canadiens fail in their quest for a fifth consecutive Stanley Cup. But something else historic was also brewing in the province that year: Laubach Literacy Canada-Quebec (LLC-Q), the forerunner of Literacy Volunteers of Quebec, now known as Literacy Quebec.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)